Wound healing activity in crude mucus extract of marine catfish,Osteogeneiosus militaris (Linnaeus) of Mumbai coast - D Deo, Ashutosh; Venkateswaran, K; Raghubir, Ram; Devaraj, M (Indian Journal of Fisheries, 2016)
Marine organisms represent a valuable source of new pharmacologically important compounds. The woundhealing activity of crude mucus extract of the marine catfish Osteogeneiosus militaris of Mumbai waters hasbeen studied using both in vivo and in vitro models. The mucus extract of O. militaris at doses of 0.25% and0.50% were found to have a higher wound contractile activity of 30% and 14.25% respectively, when comparedto the control. Wounds treated with the same dose of mucus extract for seven days had the highest level ofhydroxyproline, a marker of collagen synthesis, with values of 25.52 and 16.14 mg-1 g-1 tissue, respectively. Thecollagen crosslinking enzyme, lysyl oxidase exhibited an increasing trend with increase in dose i.e., the lysyloxidase activity was found to be dose dependent. Chick Chorioallantoic Model (CAM) studies showed angiogenicactivity of the mucus from slight to marked levels at different doses. Neovascularization at a dose of 80 g wasmarked inÂ  comparison to control. This study confirms the promising wound healing activity of crude mucusextract of the catfish O. militaris which warrants more detailed experimental and clinical studies with purifiedextract.